2014
DOI: 10.1111/jace.13140
|View full text |Cite
|
Sign up to set email alerts
|

Crack Healing by Thermal Treatment in Float Glass: The Effect of Tin

Abstract: The evolution of radial cracks generated by Vickers indentation on “tin side” of float glass is analysed when heat treated at 620°C under various atmospheres and results are compared with a previous similar study performed on the “air side” of the same glass. Results evidence that the presence and the oxidation state of tin ions has a strong influence on crack morphological changes. If the oxidation state of tin remains quasi unchanged during the heat treatment, the mechanism responsible of the crack evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…to Sn(IV) results after the ion-exchange treatment [19]. Tempered glass seems to have also higher amount of Sn(IV) that could be related with the high temperature of the thermal treatment [31] followed by the rapid cooling that stabilizes a greater amount of oxidized species. However, heat strengthening seems to have an even lower amount of Sn (IV) than annealed glass.…”
Section: Supplementary Materialsmentioning
confidence: 94%
“…to Sn(IV) results after the ion-exchange treatment [19]. Tempered glass seems to have also higher amount of Sn(IV) that could be related with the high temperature of the thermal treatment [31] followed by the rapid cooling that stabilizes a greater amount of oxidized species. However, heat strengthening seems to have an even lower amount of Sn (IV) than annealed glass.…”
Section: Supplementary Materialsmentioning
confidence: 94%
“…The densification is assumed to be brought about by the cylinders getting shorter and thicker as the sintering time progresses. The change in the geometry that leads to densification is related to reduced time, as shown in Equation (14). The densification plot is extrapolated to obtain fictitious time, t 0 , at which the density of the glass compact is zero that is used to calculate (t − t 0 ) where t is the experimental sintering time.…”
Section: Intermediate Stage Of Sinteringmentioning
confidence: 99%
“…The author concluded that depending on the atmosphere, the oxidation of tin changes, which results in different crack-healing morphologies. 14 Zaccaria et al 15 studied the thermal healing of realistic flaws in soda-lime-silica glass. The aim of this study was to understand the effect of strength recovery upon crack healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscosities of glasses and silicate melts decreases with water content, which presents as OH and molecular H 2 O . As the humid atmosphere decreases the viscosity of glass near the crack surface, the crack healing is enhanced in a moist atmosphere . The kinetics of crack healing is studied using radial cracks generated by Vickers indentation, the morphology of which changes with time by heat treatment .…”
Section: Introductionmentioning
confidence: 99%